A Complexity-Based Framework for Estimating Inspection Budgets for Transportation Infrastructure: The Case of Vietnam - Dang, Thi-Xuan-Mai; Vu, Manh-Luan; Pham, Thuy Binh; Dang, Hoang Mai (International Journal of Sustainable Construction Engineering and Technology, 2026)
Accurate and transparent estimation of inspection budgets is essential for maintaining the safety, functionality, and resilience of transportation infrastructure. In Vietnam, however, budgeting practices for bridge inspections remain constrained by outdated cost norms, inconsistent estimation methods, fragmented data systems, and limited adoption of risk-informed planning. This study develops a complexity-based framework that integrates international best practices with Vietnam’s legal and institutional context to improve inspection budget estimation. Using a mixed-methods approach—including legal and document review, comparative analysis, and validation through practical cases—the study proposes three key enhancements: (i) defining cost-driving factors within inspection terms of reference, (ii) improving cost data quality through strategic cost management initiatives, and (iii) matching estimation techniques to inspection complexity classes. The resulting framework provides a structured, scalable basis for more accurate and defensible budgeting. The findings offer actionable insights for policymakers and practitioners in Vietnam and other developing countries seeking to modernize inspection budgeting systems, strengthen resource allocation, and support long-term infrastructure sustainability.